Problem-Based Learning for Enhancing Learning Outcomes in Teaching Zakat in Islamic Elementary Schools - Sumiati (Jurnal Keprofesian Guru Keagamaan, 2025)
This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model in improving student learning outcomes on the subject of zakat in grade V at SD Negeri 002 Tapau. This study used the classroom action research method with grade V students as subjects, which was carried out through two learning cycles. Data were collected through observation and documentation to assess teacher activities, student participation, and learning outcomes. The results showed a significant increase in student engagement and learning outcomes, with the level of mastery exceeding the Minimum Mastery Criteria (KKM). These findings confirm that the PBL model is effective when applied in Islamic Religious Education, as it encourages student activity, deepens understanding of the concept of zakat, and improves the overall quality of the learning process and outcomes.